Advocacy and Justice in the Digital Era: Contemporary Challenges and Innovations in Indonesian Legal Services - Aprila Niravita; Asmarani Ramli; Windiahsari Windiahsari; Muhammad Adymas Hikal Fikri (Universitas Negeri Semarang, 2026)
This editorial introduces the key themes in the Indonesian Journal of Advocacy and Legal Services Volume 8 Issue 1 (2026), titled